KONSEP KESEJAHTERAAN SOSIAL AL-GHAZALI DALAM TUJUAN PERSPEKTIF DARI USAHA MILIK DESA - Suartini, Suartini; Syafrizal, Syafrizal (Al-Risalah, 2021)
Al-GhazÄlÄ« formulated that the concept of maslahat or social welfare or utility (common good), which is a concept that all human activities, especially in the economic field, must be carried out with the aim of benefit or social welfare, therefore it is in line with the objectives of Village-Owned Enterprises (BUM Des) in order to achieve economic equality and village development as mandated by law No.6 of 2014 concerning Villages, BUM Des was formed by the village government to utilize all human resources in order to improve the welfare of village communities in accordance with article 87 paragraph (3) of Law Number 6 of 2014 concerning Villages. The purpose of BUM Des is to improve the welfare of the village community. The research formulates problems that equate Al-GhazÄlÄ«'s perceptions of social welfare with the objectives of Village-Owned Enterprises. This research is a study using literature review. Literature review or literature research is a research that examines, reviews or critically examines the knowledge, ideas, or findings contained in an academic-oriented literature. The results of this study indicate that the BUM Des that was formed by the village with the aim of the welfare of the village community and the distribution of the results allocated for the benefit of the village community and the efforts carried out to meet community needs are in line with the concept of social welfare of Al-GhazÄlÄ«.